Atividade anti-inflamatória, antinociceptiva e antioxidante do extrato etanólico de Leonurus sibirucus L. (Lamiaceae) - Oliveira, Alan Santos (2017)
Inflammation is an important component in the development of various pathologies in which the primary process is the recruitment of leukocytes as a cause of tissue injury. The need for new compounds to treat this condition is imminent. In this context, medicinal plants represent a viable alternative for this purpose. Leonurus sibiricus L. is a plant popularly used to treat inflammation and there are few studies that confirm this use. The present study aimed to investigate the antioxidant, antinociceptive and anti-inflammatory effects of the ethanol extract of aerial parts of L. sibiricus. The total content of phenols and flavonoids, as well as the chromatographic analysis by high performance liquid chromatography were carried out to characterize the ethanol extract of L. sibiricus (EELs). In vitro experiments, the antioxidant capacity tests were carried out by elimination of 2,2-diphenyl-1-picryl-hydrazila (DPPH), 2,2'-azinobis (ABTS) and nitric oxide (NO) inhibition, inhibition of lipid peroxidation and the iron reduction potential test (FRAP). In in vivo experiments, the antinociceptive activity was evaluated through the formalin paw and hot plate and anti-inflammatory test using the edema test The results were expressed as mean ± SEM and analyzed by analysis of variance followed by Tukey's test; p<0.05 was considered significant. The contents of total phenols and flavonoids in the extract were 60.1 ± 0.1 mg of gallic acid equivalents/g of extract and 15.4 ± 0.1 mg of catechin equivalents/g of extract, respectively. In the chromatographic profile of EELs, chlorogenic acid, caffeic acid, ferric acid, p-coumaric acid and quercetin were identified. Decrease of DPPH (IC50= 267,6 μg/mL), ABTS (IC50= 7894,3 μg/mL) and NO (IC50= 266,6 μg/mL) radical was observed, as well as the increase in the reduction potential by the FRAP assay. In addition to reducing spontaneous (IC50= 652,4 μg/mL) or FeSO4-induced (IC50= 1553,3 μg/mL) lipid peroxidation in vitro. In the formalin test in the paw, administration of the EELs (400 mg / kg) reduced (p <0.05) the licking / biting time in the second phase of the test compared to the vehicle group, as did as the treatment with morphine and aspirin (p <0.05 each). On the other hand, only morphine decreased (p <0.05) this parameter in the first phase of the test. In the hot plate test, administration of the EELs at all doses did not increase the latency time of mice. In the open field test, administration of EELs to the animals did not change the distance traveled when compared to the vehicle-treated group. In the TPA-induced edema, topical administration of EELs reduced the thickness (p<0.05), MPO activity (p<0.05), TNF-α and IL-1β production (p<0.05) and lipid peroxidation (p<0.05) in the ear, as well as increased FRAP in this tissue (p<0.05). All together, these results show that EELs has anti-inflammatory, antinociceptive and antioxidant properties, supporting the popular use for the treatment of inflammatory conditions.